Feeding biology of common and blue duiker - Kigozi, Frederick (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2001)
The blue duiker, Philantomba monticola and common or grey duiker, Sylvicapra grimmia represent two of the three duiker genera as well as two of the three species occurring in Southern Africa. The two species have not been adequately studied in their habitats within the Eastern Cape Province of South Africa, and this thesis centres around their biology with focus on diet and dental microwear. Faecal analysis was used to study the diet of blue duiker at Salem in the Albany district, and of common duiker on two farms, one a predominantly cattle farm at Kasouga and the other a farm for cultivation of chicory at Grants valley, both in the Bathurst district. The validity of faecal analysis was reviewed, and its applicability to blue and common duiker assessed. The method was appropriate for diet analysis of both species, as the common duiker is shy and secretive and the blue duiker is a rare and protected species which does not habituate readily. Results showed that the blue duiker was mainly folivorous with a seasonally stable diet of 79 percent dicot foliage and only 17 percent fruit. Common duiker diet at both study sites comprised mostly dicot foliage, with only two monocotyledonous plant species. Twenty-seven and nineteen plant species were identified in the diets of common duiker at Kasouga and Grants valley respectively and the annual percentage occurrences of dicot foliage in the diets were about 99 percent at both study sites. The predominantly browsing common duiker, therefore offered negligible competition for food resources to the grazing cattle on Kasouga farm. Both blue and common duiker fed selectively, with approximately one third of the total number of plant species identified in their diets providing at least 50 percent of the food eaten annually. Ehretia rigida was the most important plant species in the diets of both duiker species. Chicory, Chichorium intybus provided more than one third (35.6 percent) of the winter diet and a substantial proportion (14.4 percent) of the spring diet of common duiker at Grants valley, thereby confirming earlier reports of this species feeding on chicory and other cultivated crops. The diet of common duiker at Kasouga did not vary seasonally but that of common duiker at Grants valley did vary and this was attributed to utilisation of chicory. Results from the dental microwear analyses did not show any significant differences in dental microwear between blue and common duiker, but supported and confirmed that the two were browsing species, characterised by many pits and few scratches on their dental surfaces. A high incidence of pits was found on the dental surfaces of both duiker species, and was attributed to utilisation of fruit in the diet.
Keywords: Duikers -- Nutrition -- South Africa -- Eastern Cape; Sylvicapra grimmia -- Nutrition -- South Africa -- Eastern Cape; Herbivores -- Nutrition; Folivores -- Nutrition; Teeth -- Abrasion